Предмет: Математика, автор: regohi

(-1 целая 1/4) + 3,6* 1 целую 5/6

Ответы

Автор ответа: snow99
3

 - 1 \frac{1}{4}  + 3.6 \times 1 \frac{5}{6}  =  -  \frac{5}{4}  +  \frac{36}{10}  \times  \frac{11}{6}  =   - \frac{5}{4}  +  \frac{6 \times 6 \times 11}{2 \times 5 \times 6}  =  -  \frac{5}{4}  +  \frac{33}{5}  =  -  \frac{25}{20}  +  \frac{132}{20}  =  \frac{107}{20}  = 5 \frac{7}{20}
Автор ответа: oksik1970
3

 - 1 \frac{1}{4} +  3.6 \times 1 \frac{5}{6}  = - 1 \frac{1}{4} +  \frac{36}{10}  \times  \frac{11}{6}  = - 1 \frac{1}{4} +  \frac{6 \times 11}{10}  = - 1 \frac{1}{4} +  \frac{3 \times 11}{5}  = - 1 \frac{1}{4} +  \frac{33}{5}  = - 1 \frac{1}{4} + 6 \frac{3}{5}  = 5 \frac{12 - 5}{20}  = 5 \frac{7}{20}
Похожие вопросы
Предмет: Математика, автор: zhumabekovaadele
Предмет: Математика, автор: GrimOptimist